2016
DOI: 10.1021/acsami.5b08452
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Slippery Lubricant-Infused Porous Surface for Inhibition of Microbially Influenced Corrosion

Abstract: Microbially influenced corrosion (MIC) accelerates the failure of metal in a marine environment. In this research, slippery lubricant-infused porous surface (SLIPS) was designed on aluminum, and its great potential for inhibiting MIC induced by sulfate-reducing bacteria (SRB) was demonstrated in a simulated marine environment. The inhibition mechanism of SLIPS to MIC was proposed based on its effective roles in the suppression of SRB settlement and isolation effect to corrosive metabolites. The liquid-like pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(80 citation statements)
references
References 39 publications
(58 reference statements)
0
77
1
Order By: Relevance
“…The porous micro-structure of the underlying layer provides numerous small "cells" that help maintain a layer of lubricant that blocks contact between other liquids and the underlying solid while increasing the available surface area [94]. Wang et al [95,96] designed and fabricated SLIPS on an aluminum substrate and found that the surface was highly resistant to sulfate reducing bacteria (SRB) adhesion and the resulting microbial corrosion in static seawater. Epstein et al [97] showed that SLIPS exhibits liquid repellency, smoothness, self-healing, and stability under high pressure, as well as a good optical transparency.…”
Section: Marine Anti-fouling Coatingsmentioning
confidence: 99%
“…The porous micro-structure of the underlying layer provides numerous small "cells" that help maintain a layer of lubricant that blocks contact between other liquids and the underlying solid while increasing the available surface area [94]. Wang et al [95,96] designed and fabricated SLIPS on an aluminum substrate and found that the surface was highly resistant to sulfate reducing bacteria (SRB) adhesion and the resulting microbial corrosion in static seawater. Epstein et al [97] showed that SLIPS exhibits liquid repellency, smoothness, self-healing, and stability under high pressure, as well as a good optical transparency.…”
Section: Marine Anti-fouling Coatingsmentioning
confidence: 99%
“…As for marine antibiofouling, the previous mentioned BMA‐EDMA slippery surface showed remarkable suppression of adhesion of both zoospores of the algae Ulva linza and cypris larvae of the barnacle Balanus amphitrite in artificial seawater in laboratory assays after infusing fluorocarbon lubricants . Similar results have been shown on aluminum based slippery coating for the prevention of microbial influenced corrosion (MIC) induced by sulfate reducing bacteria (SRB) in the sea . slippery surfaces suppress the attachment of SRB and isolate its corrosive metabolites in both static and dynamic marine conditions, which demonstrate the potential applications of slippery surfaces in the marine environment.…”
Section: Emerging Biomedical Applications Of Bioinspired Slippery Surmentioning
confidence: 99%
“…With the exceptional slipperiness of the overcoated liquid interface, LISS from both porous substrates (e.g., PTFE, BMA‐EDMA) and polymer gels (e.g., fluorogel, iPDMS) have obtained comparable antibiofouling property which could exhibit inhibition of bacteria adhesion,, surface protection from MIC, high underwater transparency and even resist the mussel attachment …”
Section: Emerging Biomedical Applications Of Bioinspired Slippery Surmentioning
confidence: 99%
“…Impregnated oil not only minimizes the direct contact of water with the solid structures but also has fluidity owing to the nature of oil, and thus can allow unique self‐cleaning and healing properties . In addition, the impregnation of oil into the surface porous structures including the AAO has been employed to prevent the corrosion of metallic materials (e.g., steel and aluminum) in marine environments …”
Section: Introductionmentioning
confidence: 99%
“…The complete impregnation of oil into the nanopores is critical for preventing the penetration of corrosive media into the pores as well as the depletion of the passivating oil out of the surface layer, which will result in greater durability as well as self‐healing property. Nevertheless, so far the complete impregnation of oil in the high‐aspect‐ratio dead‐end nanopores of the AAO layer and the resultant self‐healing capability has not yet been verified …”
Section: Introductionmentioning
confidence: 99%